Mr Wilfrid Roberts MP : inter-departmental correspondence (copy) - Tewson, Vincent
029-0162-001 F. McDonald. Secretary's. Mr. Tewson. 26th April, 1937. Mr. Wilfred Roberts, M.P. Mr. Wilfrid Roberts, M.P., wanted to see Sir Walter about sending food to Spain. I told him that he would be in meetings this week, and suggested he should come to see you tomorrow afternoon, Tuesday, at 3 p.m., and I said that Mr. Gillies might be present also. I have not yet mentioned the matter to Mr. Gillies. FEM/KMS/472. 292/946/29/162